HIV and HIV-Tat inhibit LPS-induced IL-27 production in human macrophages by distinct intracellular signaling pathways. Issue 3 (11th July 2017) - Gajanayaka, Niranjala; O'Hara, Shifawn; Konarski, Yulia; Fernandes, Jason; Muthumani, Kar; Kozlowski, Maya; Angel, Jonathan B; Kumar, Ashok
Abstract : HIV inhibition of LPS-induced IL-27 production in human macrophages affects cIAP-1-TRAF-6, PI3K, and p38 MAPKs. Abstract: Monocyte-derived Mϕs (MDMs) from HIV-infected patients and MDM infected in vitro with HIV exhibit a reduced ability to secrete various cytokines, including IL-12. Recently, IL-27, an IL-12 family cytokine, was shown to inhibit HIV replication in Mϕ. Whether HIV infection or HIV accessory protein(s) impact IL-27 production in Mϕs remains unknown. Herein, we show that in vitro HIV infection, as well as intracellular HIV-Tat (Tat) and Tat peptides, inhibit LPS-induced IL-27 production in human MDMs, suggesting impairment of the TLR4 signaling pathway. To understand the signaling pathways governing HIV or Tat-mediated inhibition of LPS-induced IL-27 production, we first demonstrated that p38 MAPK, PI3K, Src-homology region 2 domain-containing tyrosine phosphatase 1 (SHP-1), and Src kinases regulate LPS-induced IL-27 production in MDMs. Tat caused down-regulation of TNFR-associated factor (TRAF)-6 and inhibitor of apoptosis 1 (cIAP-1) and subsequently decreased phosphorylation of downstream PI3K and p38 MAPKs, which were implicated in LPS-induced IL-27 production. Whereas SHP-1 and Src kinases regulated LPS-induced IL-27 production, Tat did not inhibit these kinases, suggesting that they were not involved in Tat-mediated inhibition of LPS-induced IL-27 production. In contrast to Tat, in vitro HIV infection of MDM inhibited LPS-induced IL-27 production via inhibition of p38 MAPK activation. Overall, HIV and Tat inhibit LPS-induced IL-27 production in human macrophages via distinct mechanisms: Tat through the inhibition of cIAP-1–TRAF-6 and subsequent inhibition of PI3K and p38 MAPKs, whereas HIV through the inhibition of p38 MAPK activation.